1976
DOI: 10.1111/j.1600-0536.1976.tb03012.x
|View full text |Cite
|
Sign up to set email alerts
|

Lymphomatoid contact dermatitis A syndrome produced by epicutaneous hypersensitivity with clinical features and a histopathologic picture similar to that of mycosis fungoides

Abstract: Four cases have been studied which were clinically suggestive of mycosis fungoides because of their infiltrated plaque-like lesions, but in which the suspicion of a topical hypersensitivity arose when a positive patch test was obtained with the striker part of a box of matches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
1
2

Year Published

1983
1983
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(42 citation statements)
references
References 1 publication
2
37
1
2
Order By: Relevance
“…Since this study did not include cases of eczema, this important aspect will need to be the subject of a separate analysis. 15,16 A previous study by Ardigò et al on the description of RCM findings of discoid lupus suggested the morphologic findings of epidermal disarray and ill-defined cell demarcation as being a variant of spongiosis. 17 While this feature lacks an unequivocal description, there is evidence that this aspect may be comparable to features observed in MF, namely "loss of demarcation," "hole-like perforations," and "epidermal disarray.…”
Section: Discussionmentioning
confidence: 99%
“…Since this study did not include cases of eczema, this important aspect will need to be the subject of a separate analysis. 15,16 A previous study by Ardigò et al on the description of RCM findings of discoid lupus suggested the morphologic findings of epidermal disarray and ill-defined cell demarcation as being a variant of spongiosis. 17 While this feature lacks an unequivocal description, there is evidence that this aspect may be comparable to features observed in MF, namely "loss of demarcation," "hole-like perforations," and "epidermal disarray.…”
Section: Discussionmentioning
confidence: 99%
“…In two reported cases, the dense infiltrate was initially diagnosed as consistent with MF. 8,9 In each case, the correct diagnosis of allergic contact dermatitis was eventually established after positive patch reactions to allergens known to be in contact with the biopsy site were found: the first was a biopsy of hand dermatitis, with an allergy to the striker part of a matchbox, and the second was a biopsy of a left posterior thigh dermatitis, with an allergy to a rubber eraser the patient carried in his back pocket. Ackerman et al also warned that allergic contact dermatitis could closely mimic MF, reporting several cases of spongiotic dermatitis, most often allergic contact dermatitis, with foci of atypical mononuclear cells that he cautioned could be easily misdiagnosed as Pautrier microabscesses.…”
Section: Lymphomatoid Dermatitismentioning
confidence: 99%
“…It is the later subacute to chronic ACD, with mild spongiosis, intraepidermal lymphocytes and Langerhans cells, and a bandlike, dermal lymphocytic infiltrate with associated fibrosis that most closely simulates MF (Figure 3, A through C). 20,27,[32][33][34][36][37][38] In these later lesions, scattered, dyskeratotic keratinocytes may be identified. Langerhans cell microabscesses (LCMs), which are evidence of a spongiotic process, are frequently present in the epidermis.…”
Section: -34mentioning
confidence: 99%